Forest rehabilitation in Vietnam: histories, realities and future - Jong, W. de; Do Dinh Sam; Trieu Van Hung (Center for International Forestry Research, 2006)
This report assesses the experiences of forest rehabilitation in Vietnam and draws strategic lessons from these experiences to guide new forest rehabilitation projects. The report highlights lessons from Vietnam's experiences that will be helpful beyond the country border. This report has the following structure: the remainder of chpater one provides the conceptual clarification and theoritical underpinnings for the study and introduces the methodology. Chapter two provides background information and context for the outcomes of forest rehabilitation in Vietnam, including basic information on Vietnam, its forest cover, forestry sector and policies that are relevant to forestry and forest rehabilitation. Chapter three gives an overview of forest rehabilitation in Vietnam from its inception in the 1950s until today, as the country carries out its latest nationwide forest rehabilitation effort, the 5 million hectares reforestation project. Chapter four analyses in detail forest rehabilitation project that were analysed in the field study carried out as part of this study. Chapter five draws lessons from the report.